Scale Development for Assessing Awareness, Attitudes, and Practices of Indian Knowledge Systems (OCEM Journal of Management, Technology & Social Sciences, 2026)
The Indian Knowledge System (IKS) houses knowledge assets in health, education, philosophy and sustainability right from the immemorial times. However, in spite of the fact that it was becoming increasingly significant, there has been scant research on an overall survey of people’s awareness, attitude and practice (AAP) towards IKS. The purpose of this study is to develop and validate a psychometric scale that can capture AAP towards Indian Knowledge systems (as such) on the ground realistically and reliably so as to provide an easily usable tool for research, policy making and educational/learning systematization. The authors used a simultaneous approach design, in the first phase, items were generated from a review of the literature, expert opinion and focus groups. Content validity was assessed by a expert team and pilot study was followed by a large survey on respondents from different parts of India. EFA determined latent structure and measurement model was tested by CFA.An internal reliability and convergent/discriminant validity analyze were performed. The final scale included three main factors that have been named as Awareness, Attitudes and Practices. The three factors showed high reliability, acceptable fit with the measurement model and strong evidence for convergent and discriminant validities. Each item on the scale read and discussed, to confirm that it was clear, culturally acceptable as a function of content analysis, and had good psychometric properties.The research offers a valid approach to assessing AAP toward IKS. The tool can be employed by researchers, educators and policy makers for measuring perceptions and learning about IKS in curricula/ programmes, dissemination of methods for promoting culture conservation and sustainable development.